Early Childhood Caries (ECC) Prevalence and Background Factors: A Review - Congiu, Giovanna; Campus, Guglielmo; Lugliè, Pier Franca (Oral health & preventive dentistry, 2014)
To describe the prevalence of early childhood caries (ECC) by reviewing published reports and to assess the role of background factors in ECC prevalence. The studies included here consisted of reviews, meta-analyses and randomised clinical trials (RCT) which assessed the prevalence of ECC and included more than 100 subjects and subjects without any stated medical condition. These were in vivo studies published between January 1, 2000 to May 31, 2011. The patients' age range for inclusion was zero (0) to five (5) years of age. Database searching showed 411 findings as potentially eligible. After abstract review, eight (8) papers were retrieved as full text and assessed for eligibility: three using ECC as mesh word, four using the term early childhood caries and one using severe-ECC (S-ECC) as mesh word. The main risk factor for ECC is the low socioeconomic status of the parents. ECC is a public health problem and it requires the involvement of all health professionals that provide care to children together with efforts from family members.